Pengaruh Berbagai Tingkat Protein Pakan Campuran BR1, Jagung Kuning dan Tepung Gaplek terhadap Bobot dan Persentase Giblet Ayam Kampung Super - Kastalani Kastalani; Yemima Yemima; Eving Febrianti (Fakultas Peternakan Universitas Kristen Palangka Raya, 2022)
The purpose of this study was to determine the effect of various protein levels of BR1 mixed feed, yellow corn, and cassava flour on weight and percentage of super free-range chicken giblets. The implementation of this research took place at the practice location of the Faculty of Animal Husbandry, Christian University of Palangka Raya, Jalan G.S Rubay Palangka Raya. This study used a completely randomized design (CRD) with 5 treatments with 4 replications, namely Treatment A = Feed with 20% protein content, Treatment B = Feed with 19% protein content, Treatment C = Feed with 18% protein content and Treatment D = Feed with protein content of 17%. From the results of the stud, it was shown that the various levels of protein levels mixed with BR1, yellow corn, and cassava flour did not have a significant effect on the weight and percentage of giblets in Joper chickens. Keywords: Free range chickens, giblets, mixed feed